Respiratory disturbances in congenital heart disease - Davies, H (1965)
The work described in this thesis has been carried out over the period 1958-1965, having been begun during the tenure of a residency at the University of Colorado, Denver, U.S.A. At this time, surgery for the closure of septal defects was being actively carried out, and interest was aroused, in two clinical features which were apparent from close contact with this programme. The first was the nature of the chest deformities associated with septal defects; the second, the striking alleviation of symptoms which followed successful closure of these defects. The reasons for these phenomena were by no means clear and the subsequent work has been concerned with an attempt to understand them. (Cont.)